Statistical evaluation of the epoxidation of esters from vegetable oils and optimization of reaction conditions - Hájek, Martin; Kocián, David; Douda, Miroslav (Elsevier, 2023)
The increasing glycerol consumption will result in an issue for further applications of methyl esters, which are produced together with glycerol by transesterification of vegetable oils/animal fats on industrial scale. One possibility is the formation of bio-epoxides, which can be used for bio-lubricants, precursors for chemicals or CO2 capture, and so they can replace products from crude oil. Therefore, the mathematical models describing epoxidation of methyl esters, i.e., the influence of reaction conditions (time, temperature, etc.) on the properties of epoxides (iodine and epoxide values, relative conversion to oxirane, etc.) were created/calculated to decrease the production cost. It was found that (i) higher initial iodine value of esters, (ii) higher reaction temperature, (iii) higher concentration of formic acid and (iv) longer reaction time caused more formed epoxides. In contrast, a higher concentration of hydrogen peroxide caused epoxide ring opening and the formation of side products. The catalyst (H2SO4) and the intensity of stirring were statistically insignificant. The drying of epoxides was carried out by distillation and improved by the addition of a small amount of methanol. The models allow the synthesis of epoxides with desired properties, which are biodegradable and nontoxic with variety of applications.
Statistické vyhodnocení epoxidace esterů z rostlinných olejů a optimalizace reakčních podmínek
Keywords: Epoxidation; Methyl esters; Vegetable oils; Statistical evaluation; Iodine value; epoxidace; metylester; rostlinné oleje